Geochemistry of Garga-Sarali intrusive granitoids (central domain of the central African fold belt in Cameroon): petrological implication - Isaac, Daama; Gbambie Isaac Bertrand, Mbowou; Ngounouno Fadimatou, Yamgouot; Mama, Ntoumbe; IsmaÃ¯la, Ngounouno (International Journal of Advanced Geosciences, 2020)
The Garga-Sarali granitoids outcrop in form of large slabs and undistorted large blocks, into a schisto-gneissic basement. These rocks contain mainly muscovite and microcline, followed by K-feldspar, quartz, biotite, pyroxene, zircon and oxides, with coarse-grained to fine-grained textures. Geochemical analysis show that it belongs to differentiated rocks group (granodiorite-granite) with high SiO2 (up to 72 wt%) contents. Their genesis was made from a process of partial melting and fractional crystallization. These rocks are classified as belonging to I- and S-Type, meta-peraluminous, shoshonitic granites; belonging to the domain of volcanic arcs. The rare earth elements patterns suggest a source enriched of incompatible elements. The Nb-Ta and Ti negative anomalies from the multi-element patterns are characteristics of the subduction domains.Â Â